(untitled) (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2021)
In this work, we used numerical modeling of the spread of pollutants due to the occurrence of an exothermic chemical reaction near the roadway inside a street canyon. In the course of the study, the dispersion properties of gas when colliding with idealized buildings were studied, an assessment was made that characterizes the spread of the pollutant concentration, and the process of the appearance of zones with increased turbulence, in which vortices are formed, which impede the ventilation properties of the horizontal flow, was analyzed. The reactive gases in question are NO and NO2 emitted into the canyon area as a result of ozone traffic. The results obtained can be used in the future for use by transport designers and road engineers, whose goal is to reduce the concentration of nitrogen oxides near the pedestrian zone of the city.